Building Pounding Damages Observed during the 2015 Gorkha Earthquake - Shrestha, B.; Hao, Hong (American Society of Civil Engineers, 2018)
The purpose of this paper is to present information on the damage resulting from pounding between adjacent buildings during the 2015 Gorkha earthquake. The cases of pounding observed in the affected region of central Nepal are classified into five damage severity levels. Typical and unique cases of pounding damage are highlighted and discussed. Although poundings between adjacent buildings were rarely observed in Kathmandu Valley, it was relatively more frequent in hilly regions. Pounding events observed in Kathmandu Valley were primarily confined to multistoried RC structures. Pounding damage was also observed between masonry structures particularly at hilly urban settlements in Kabrepalanchok and Sindhupalchok district. Multiple cases of pounding between masonry structures with adjacent RC structures were also observed. Pounding damage observed in the field are presented in terms of various building configurations for the three categories of buildings involved, i.e., between RC structures, between masonry structures, and between RC and masonry structures. Pounding resulted in severe damage to masonry buildings. Based on the observations, building configurations that are vulnerable to pounding damage and distributions of pounding damage based on locality are discussed.